Lactate and lactylation in intervertebral disc degeneration - Liu, Yadong; Yang, Jihao; Wang, Zihui; Fu, Jing; Liu, Hongpeng; Lu, Zekun; Dong, Jinwei; Li, Zhong; Mao, Qiuyue; Li, Chunlan; Ma, Hui (Frontiers in Molecular Biosciences, 2025)
The unique hypoxic microenvironment of the intervertebral disc, characterized by its avascularity and restricted nutrient exchange, drives a shift in cellular metabolism towards anaerobic glycolysis. This metabolic adaptation results in the accumulation of significant lactate levels. Increasing evidence indicates that lactate plays a pivotal role in regulating cell differentiation and fate in both physiological and pathological contexts, particularly in complex conditions such as degenerative diseases and cancer. Lactate is not merely a metabolic byproduct; it also modulates cellular signaling pathways and promotes lactylation. In the lactate-enriched microenvironment of the intervertebral disc, understanding the regulatory mechanisms of lactate and lactylation is essential for mitigating intervertebral disc degeneration and improving therapeutic outcomes. Targeting lactate production and transport—particularly through lactate dehydrogenases (LDHs) and monocarboxylate transporters (MCTs)—holds significant therapeutic promise. This review highlights the critical role of lactate in intervertebral disc degeneration progression and discusses potential therapeutic strategies aimed at modulating lactate metabolism to enhance treatment efficacy.